Women enter the picture - United Nations Educational, Scientific; Cultural Organization; Lucía Iglesias Kuntz (The UNESCO Courier, 2024)
Long confined to the roles of copyist, patron or muse, women artists have been enjoying greater recognition in recent years, as demonstrated by museum acquisition policies and the space reserved for them at major exhibitions. But despite the efforts of many institutions to feminize their collections, parity is still a distant goal.